Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (3) (Apidae, Colletinae). Revision der Hylaeus-nivalis-Gruppe in Europa und Klärung weiterer westpaläarktischer Arten. - Dathe, Holger H. (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The discovery of three new species, Hylaeus (H.) hellenicus sp. n., H. ibericus sp. n. and H. pyrenaicus sp. n., gave rise to a revision of the European taxa of the Hylaeus nivalis group; a key to the males is given. In the Hylaeus communis group, in the Westpalaearctic region two morphologically separated species circles are defined: communis s. str. und deceptorius. New synonymy: Hylaeus (H.) deceptorius (Benoist) = Prosopis communis cretica Warncke syn. n. The Hylaeus garrulus group from the Iberian peninsula consists of three species. Their distribution has to be re-examined, a key is provided. One species is new, H. (Prosopis) convergens sp. n. The following additional species are described: H. (Paraprosopis) emir sp. n. (UAE), H. (Koptogaster) tetris sp. n. (Turkey). H. (Hylaeus) cervinus (Warncke, 1992) is redescribed. Keywords Hymenoptera, Apidae, Colletinae, Hylaeus, Palaearctic region, taxonomy, new species, new synonymy, determination key. Nomenclatural Acts hellenicus Dathe, 2000 (Hylaeus (Hylaeus)), spec. n. ibericus Dathe, 2000 (Hylaeus (Hylaeus)), spec. n. pyrenaicus Dathe, 2000 (Hylaeus (Hylaeus)), spec. n. tetris Dathe, 2000 (Hylaeus (Koptogaster)), spec. n. emir Dathe, 2000 (Hylaeus (Paraprosopis)), spec. n. convergens Dathe, 2000 (Hylaeus (Prosopis)), spec. n. teruelus (Warncke, 1981) (Hylaeus (Prosopis)), stat. n. hitherto Prosopis garrula teruela cretica Warncke, 1981 (Prosopis communis), syn. n. of Hylaeus (Hylaeus) deceptorius (Benoist, 1959)